1998
DOI: 10.1111/j.1447-0756.1998.tb00109.x
|View full text |Cite
|
Sign up to set email alerts
|

Pityriasis Lichenoides et Varioliformis Acuta in Pregnancy: A Case Report

Abstract: If pityriasis lichenoides et varioliformis acuta (PLAVA) exists in the vagina or cervical os of the uterus, it may cause premature labor and premature rupture of the membranes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 2 publications
0
12
0
Order By: Relevance
“…There are also isolated reports of the development of PLEVA during pregnancy. [15][16][17] Pityriasis lichenoides in the pediatric population Epidemiologic data collected from the review of various studies of pediatric cases of pityriasis lichenoides are presented in Table II. [18][19][20] These studies showed peaks at 5 and 10 years of age, with predominance in males.…”
Section: Epidemiology Pityriasis Lichenoides In the General Populationmentioning
confidence: 99%
“…There are also isolated reports of the development of PLEVA during pregnancy. [15][16][17] Pityriasis lichenoides in the pediatric population Epidemiologic data collected from the review of various studies of pediatric cases of pityriasis lichenoides are presented in Table II. [18][19][20] These studies showed peaks at 5 and 10 years of age, with predominance in males.…”
Section: Epidemiology Pityriasis Lichenoides In the General Populationmentioning
confidence: 99%
“…In addition, Fukada et al . 3 support the possibility that PLEVA in pregnancy may cause premature labour and premature rupture of the membranes. In our case there were no signs of premature labour, although we cannot exclude such a possibility in cases presenting a prolonged course of the disease due to inappropriate or late therapy.…”
Section: Discussionmentioning
confidence: 52%
“…The subject reported by Fukada et al . 3 had had a documented diagnosis of PLEVA even before pregnancy, which rapidly underwent clinical remission with hydrocortisone ointment. In our case the anamnesis indicated that there was probably a previous eruption of PLEVA, but there were no certain data to confirm this.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only two previous cases of PLEVA during pregnancy have been reported in the literature 3,4 . No signs of infection were observed in either case, and the disease was successfully treated with systemic antibiotics.…”
mentioning
confidence: 78%